A production system study of GENCAP - Urgino, Suzanne Margaret D. (College of Engineering, 1995)
Gencap is a manufacturing company in San Juan Manila. They produce different types of headgear. Most of the products they make are baseball caps. Gencap is a member of a group of companies under Saldana Incorporated. Our group has decided to concentrate on the production process of this company. We have discovered that their main problem is delays. Among these problems are frequent breakdown of machines, delays in subcontracted embroidery, excessive transportation of materials and bottlenecks in production. We then analyzed the problems and came up with alternatives to solve these problems. From this analysis, we have made recommendations on how to cut down on delays. first we recommended that an in house repairman be hired. Then we designed a scheduling system for production. A new layout was designed to minimize transportation. We also recommended that lot sizes of fifty be used for production, a manual embroidery be purchased and individual housekeeping be implemented.